CASE REPORT: MYASTHENIA GRAVIS TYPE ANTI-MUSK (CIPEEX, 2022)
MYASTHENIA GRAVIS IS A DISEASE THAT GENERATES STRENGTH LOSS IN CERTAIN MUSCLE GROUPS, USUALLY CAUSED BY THE TRANSMISSION FAILURE OF THE ACETYLCHOLINE RECEPTOR (ACRH) IN THE SYNAPTIC SLIT OF THE NEUROMUSCULAR JUNCTION. IN THE CASE REPORT, THE PATIENT, UNLIKE THE USUAL MYASTHENIA GRAVIS PATIENTS, HAS THE ANTI-MUSK TYPE, THAT HAD ITS MAJOR MANIFESTATION IN HER SECOND PREGNANCY. SHE PRESENTED THE FIRST SYMPTOMS EVEN BEFORE ANY OF HER PREGNANCIES, BUT THEY PASSED IN A FEW DAYS, WHICH IS WHY SHE DID NOT SEEK HELP IN 2018. IT EVOLVED DURING HER PREGNANCY IN 2021, WHERE SHE HAD DIFFICULTY PERFORMING THE VOMITING REFLEX, SHE ALSO HAD SPEECH DISORDERS AND DIFFICULTY SWALLOWING. EVEN AFTER THE DIAGNOSIS, IN 2021, DURING A MIASTENIC CRISIS SHE WAS HOSPITALIZED FOR POOR NUTRITION AND TO RECIEVE IMMUNOGLOBULIN. THE DIFFICULTY OF THE THE DIAGNOSIS AND HEALTH CARE CONCERNING MYASTHENIA GRAVIS WAS CONFIRMED DURING HER PREGNANCY, BECAUSE CHILD BEARING IS A PERIOD MARKED BY MANY ENDOCRINE VARIATIONS AND IMMUNOLOGICAL ACTIVITY. THIS REPORT CONTRIBUTES TO A LIMITED NUMBER OF WOMEN WHO HAVE A NORMAL PREGNANCY, BUT WHO ALSO SUFFER FROM MYASTHENIA GRAVIS AND ITS PARTICULARITIES.
Keywords: Myasthenia Gravis; anti-musk; pregnancy